Perniagaan Online Syariah: Suatu Kajian dalam Perspektif Hukum Perikatan Islam - Suhartono - Suhartono (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2010)
Along the vast development in information technology, it creates a new variant in business relation, that once was primarily physical with papers as the transaction mechanism tools, shifts into a more virtual relationship pattern using digital media or well known as electronic commerce (ecommerce). There has been a transformation in the jurisdictional review towards agreement forms, from the conventional trading using textual document with “tinta basah” and physical contact in a real space, into a digital model where all the documents are made in a cyber space.This transaction model provides several benefits within its operational, nevertheless its presence also emerges new complex legal problems regarding the legality of a contract or an agreement, especially in the Islamic law perspective. Does an Islamic bonding law also accommodate this ecommerce transaction model?